EFFECTIVENESS OF GREEN TEA FEEDING TO DECREASE CHOLESTEROLLIN HIPERCOLESTROL PATIENTS AT VILLAGE TUNGGAL PAGER DISTRICT PUNGGING MOJOKERTO REGENCY - Anik Supriani; Nur Chasanah; Henny V Vidia Effendy; Surya Mustika Sari; Heppy Rina Mardiana; Tri Ayu Widiyaswari (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Cholesterol disease is commonly suffered by obese people but did not rule out skinny people can also experience it. Green tea is one method in the management of cholesterol reduction in non-pharmacology. Green tea has the benefit of lowering cholesterol. The purpose of this researcher to analyze the effectiveness of green tea to decrease cholesterol. The design of this study used pre-experiment with one group pre-test posttest. The population of 21 respondents using non-probability sampling with total sampling technique. The variables of this study were cholesterol first performed cholesterol assessment, independent variables Effectiveness of green tea and dependent variable decreased cholesterol levels. The results before the green tea were given most of the high cholesterol as many as 13 respondents (61.9%), after being given a green tea for one week most of the cholesterol to 13 respondents (61.9%). The Wilcoxon statistic test obtained a significant value of 0.005 and showed that there was a considerable effect of green tea on cholesterol reduction. The conclusion from the researchers is there is a significant effect of the effectiveness of green tea on changes in cholesterol levels. Cholesterol treatment performed twice a day morning and night regularly for one week. This research can also be applied in nursing care on respondents who experienced cholesterol and as well as prevention efforts cholesterol.